Mapping Research Developments on Mathematics Communication: Bibliometric Study by VosViewer - Ismail Hanif Batubara; Sahat Saragih; Edi Syahputra; Dian Armanto; Indah Purnama Sari; Baihaqi Siddik Lubis; Eko Febri Syahputra Siregar (STAI Hubbulwathan Duri, 2022)
This research aims to determine the map of the development of research on Mathematics Communication, namely a study of bibliometrics by VosViewer. The study was conducted starting in January 2021 by searching the keyword “Mathematics Communication” in the Science Direct database and choosing the open access system. The search result data is then stored in the form of a Research Information System (RIS) and analyzed descriptively using VosViewer to see developments on the topic from year to year, the types of documents that are widely published, the name of the author who has discussed the most about the case, the name of the publishing institution and the topics that appear most frequently from thousands of journals that have been processed using VosViewer. The results showed that the map of the development of research on Mathematics Communication has existed since 1997 and increases rapidly from year to year. The article that publishes the most on this topic is Research Articles with the publisher’s name Procedia Computer Science as many as 2662 documents. Meanwhile, the author who published the most on this topic was Yusof, Yudariah Mohammad, until May 28, 2021. The most dominant issue that appears was “communication”, followed by the topic of “systems” and “students”. Network visualization shows that a line demonstrates the relationship between issues between the descriptors in each field. The more relationships between the lines indicate the closer relationships between documents.ch on that topic.: Indicate the main conclusions or interpretations.